Các yếu tố tác động đến chính sách cổ tức của doanh nghiệp Việt Nam: Tiếp cận bằng hồi quy phân vị - Trần Thị Tuấn, Anh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
The dividend policy is one of the most important parts within corporate finance. Various studies have been conducted to determine the factors affecting firms’ dividend policy. This study provides empirical evidence regarding the determinants of dividend policy in Vietnam, using data from 238 listed firms in Vietnam stock market during the 2008–2013 period and quantile regression. The results demonstrate that the expected dividend payout ratio relies on return on equity, growth, risk, and ownership structure. The impact of these factors varies throughout the distribution of dividend payout ratio. The higher the percentile of dividend payout ratio, the more profound the effect of return on equity and growth on dividend payout ratio. On the contrary, the higher the percentile of dividend payout ratio, the less powerful the effect of risk and foreign ownership on dividend.
Keywords: Dividend policy; dividend payout ratio; panel data; quantile regression